Foreign aid, domestic savings and economic growth : some evidence from the ECCB area - Campbell, Richard (1999)
Examines the empirical relationship between foreign aid, domestic savings and economic growth in the independent countries in the Eastern Caribbean Central Bank (ECCB) area over the period 1980-1995. Looks at the role of development finance in the process of economic development in the context of micro states particulary vulnerable to external shocks.